Pengembangan Media Pembelajaran Materi Bangun Ruang Sisi Datar Berbasis Etnomatematika Menggunakan Ispring Suite - Hasna Nabila; Farida Nursyahidah; Dina Prasetyowati (Scholaria: Jurnal Pendidikan dan Kebudayaan, 2023)
Responses and positive attitudes of students towards mathematics are the key to success in learning. Therefore, teachers are required to be able to innovate in learning activities. With the rapid advancement of technology, it can be used as a motivation to develop innovative learning media that can support learning activities. In this study, the aim was to develop an ethnomathematics-based learning media using a valid Ispring Suite. This research is research and development with the ADDIE model which consists of 5 stages, namely analysis, design, development, implementation, and evaluation. However, in this study, the implementation was limited to the development stage. The data collection instrument in this study was a validation sheet filled out by media experts and material experts. The data analysis technique used in this research is descriptive analysis technique. Learning media is appropriate based on the assessment of media experts who get a score of 94.00% in the "Very Good" category and the results of the assessment of material experts who get a score of 95.56% in the "Very Good" category.